Robotic-assisted partial nephrectomy: surgical technique using a 3-arm approach and sliding-clip renorrhaphy - Cabello,Jose M. (2009)
INTRODUCTION: For the treatment of renal tumors, minimally invasive nephron-sparing surgery has become increasingly performed due to proven efficiency and excellent functional and oncological outcomes. The introduction of robotics into urologic laparoscopic surgery has allowed surgeons to perform challenging procedures in a reliable and reproducible manner. We present our surgical technique for robotic assisted partial nephrectomy (RPN) using a 3-arm approach, including a sliding-clip renorrhaphy. MATERIAL AND METHODS: Our RPN technique is presented which describes the trocar positioning, hilar dissection, tumor identification using intraoperative ultrasound for margin determination, selective vascular clamping, tumor resection, and reconstruction using a sliding-clip technique. CONCLUSION: RPN using a sliding-clip renorrhaphy is a valid and reproducible surgical technique that reduces the challenge of the procedure by taking advantage of the enhanced visualization and control afforded by the robot. The renorrhaphy described is performed under complete control of the console surgeon, and has demonstrated a reduction in the warm ischemia times in our series.